The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.anclin.2021.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesiology and Critical Care Response to COVID-19 in Resource-Limited Settings

Abstract: Synopsis It is difficult to predict the future course and length of the ongoing COVID-19 pandemic, which has devastated healthcare systems in low- and middle-income countries (LMICs). Anesthesiology and critical care services are hard hit as many hospitals have stopped performing elective surgeries, staff and scarce hospital resources have been diverted to manage COVID-19 patients, and several makeshift COVID-19 units had to be set up. Intensive care units are overwhelmed with critically ill patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Another study reported a lack of infrastructure, such as a central pipeline for oxygen, in most of the government-funded hospitals in Nepal. As recommended by the World Health Organization (WHO), there should be 2.3 doctors per 1000 persons; however, this study reported that only 1 doctor was available per 1000 persons in Nepal [82]. The limited number of ICU units in various countries of Southeast Asia is presented in Figure 1 (yellow).…”
Section: Resource Constraints About High Population and Limitations O...mentioning
confidence: 78%
“…Another study reported a lack of infrastructure, such as a central pipeline for oxygen, in most of the government-funded hospitals in Nepal. As recommended by the World Health Organization (WHO), there should be 2.3 doctors per 1000 persons; however, this study reported that only 1 doctor was available per 1000 persons in Nepal [82]. The limited number of ICU units in various countries of Southeast Asia is presented in Figure 1 (yellow).…”
Section: Resource Constraints About High Population and Limitations O...mentioning
confidence: 78%
“…This is possibly the result of the general trend of nonoperative management for acute appendicitis in recent years, 15 in conjunction with the reduction in health care resources during the pandemic that led the medical teams to pursue less burdensome solutions for common clinical situations. 16 …”
Section: Discussionmentioning
confidence: 99%
“…There is disagreement on the rationale principle behind the just allocation during the crisis [24][25][26][27][28]. A requirement of strengthened national guidance for the protocol and policy for ICU triaging [29] was highlighted. To conduct a deeper assessment, ICU triage frameworks for the South Asian countries were revisited.…”
Section: Theme 2: Disagreements On the (Ethical) Frameworkmentioning
confidence: 99%